Utilization of Canva Application to Increase Student Creativity in Learning: Pemanfaatan Aplikasi Canva untuk Meningkatkan Kreativitas Siswa dalam Belajar - Putri, Dian Puspita Salsabilla; Rochmaniah, Ainur (House of Wisdom: Journal on Library and Information Sciences, 2025)
New media is a form of communication and information technology development. New Media describes a communication process that can be accessed anywhere and at an unlimited time. New Media currently has a lot of effects, there are positive effects and negative effects, the positive effects that arise include efficiency in communication, ease of getting needs, and many more. In education, new media has also been used to help in the learning process. This study aims to describe how to utilize a new media in the learning process of high school students, one of which is using the Canva application and also knowing the satisfaction of using the Canva application. The method used in this study is a qualitative analysis using the application of the theory of uses and gratification which was conducted with questions and answers with several students of SMA Negeri 4 Sidoarjo from various specialization classes to find out how to use and apply the Canva application in the learning process. The results of this study showed that students felt helped and satisfied by using the Canva application because it made it easier for them to create materials or assignments and increased students' creativity. Highlights: Canva enhances creativity and eases assignment creation. Students find learning more engaging with visual tools. Qualitative study shows high satisfaction using Canva in class. Keywords: Canva, Learning Process, Implementation, High School Students